ANALISIS HUKUM PENGLIBATAN WANITA SEBAGAI PENGEBOM BERANI MATI BAGI KUMPULAN EKSTREMISME AGAMA: A Jurisdiction Analysis on Women’s Involvement as Suicide Bombers for Religious Extremist Groups - Abd Razak, Muhd Imran; Ramli, Mohd Anuar; Yusof @Salleh, Muhammad Yusri (Jurnal Fiqh, 2023)
Suicide bombing refers to someone who carries out a bomb attack with the intention of killing themselves as well as others. The destruction of human life, particularly involving women, without proper justification is considered contrary to religious and humanitarian values. However, there are extremist groups that use women to carry out suicide attacks that are oriented around religious arguments. Therefore, this study was conducted to analyze the fiqh perspectives on suicide attacks, particularly those carried out by women in the Islamic State (IS) group. This qualitative study used a selected informant interview approach in addition to document analysis of the IS group’s Dabiq magazine and other written materials. The results of the study show that suicide bombings, lone wolf attacks, and the like by women in the IS group against any infidels or those considered apostates are actions that are contrary to Islamic teachings. They are considered forbidden and sinful. However, scholars have differing views regarding suicide bombers that are specific only to the context of the Palestinian state and not other Islamic territories.